The Effect of Social Media Marketing on Hedonic Shopping Value Through Online Impulsive Buying of Fashion Products (Research On Generation Z In Bandung) - Febrian Eko Saputra; Akbar Riskal Amani (Asian Journal of Social and Humanities, 2023)
This study aims to determine and analyze the influence of social media marketing on impulsive purchases and hedonic shopping values and to analyze the role of impulsive purchase reactions that mediate hedonic shopping values. The target of this research is all online consumers in Bandung City aged between 18-25 years as many as 150 respondents. Samples were taken using non-probability techniques, with purposive sample techniques and then the data obtained from the samples were analyzed using Partial Least Square (PLS) with path analysis. The results of the study show that there is a significant influence between social media marketing on hedonic shopping value and there is a significant effect between social media marketing on impulsive purchases and a significant effect between social media marketing on hedonic shopping value through impulsive purchases, and this indicates that social media marketing affects hedonic shopping value both directly and through impulsive purchases.